The Influence of Organizational Commitment and Internal Control on Fraud Prevention with Good Governance as a Moderation - Anita Mustika Sari; Supramono Supramono; Ardiani Ika Sulistyawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The fraud phenomenon and the results of the 2023 SPI indicate that the risk in the management of procurement of goods and services in Regional Government G is still at alert status. This study aims to analyze the effect of the internal control system and organizational commitment on fraud prevention, as well as the role of Good Governance as a moderating variable. This study contributes to the development of financial management science and provides practical recommendations for governments and companies in formulating procurement policies. This study uses quantitative methods with surveys and experiments. The study population included 257 employees involved in procurement, with a sample of 209 respondents selected through purposive sampling. Data were collected through a Likert-based questionnaire and analyzed using Partial Least Squares (PLS) with SmartPLS. The results showed that organizational commitment and internal control systems had a positive effect on fraud prevention. Good Governance moderated the effect of organizational commitment positively, but weakened the effect of the internal control system. The implications of the theory based on agency theory indicate that good governance limits the opportunity for deviation through transparency and accountability. Recommendations include increasing anti-corruption training, strengthening supervision, digitalizing procurement, and optimizing the public complaint system. Further research is suggested to add variables such as leadership integrity and organizational culture to enrich the understanding of fraud prevention.